Indium-catalysed ring opening of 2-hydroxybutyrolactone through the cleavage of C(sp$^3$)–O bond - Aoun, Sameh; Massouh, Joe; Scornet, Noémie; Giordano, Laurent; Tenaglia, Alphonse; Buono, Gérard; Rey, Patrick; Bellière-Baca, Virginie; Hérault, Damien (Comptes Rendus. Chimie)
The ring opening by the cleavage of the C(sp$^3$)–O bond of 2-hydroxybutyrolactone with (ethylthio)trimethylsilane was effectively catalysed by indium triiodide. Screening the reaction conditions allowed optimizing the ring opening. The effect of the nucleophile/catalyst ratio on the reaction efficiency has also been demonstrated. After optimization, 2-hydroxy-4-(ethylthio)butyric acid was isolated with an excellent yield (85%), thus making this method useful for the preparation of methionine analogues.